The Effect of Physicochemical Properties and Elemental Composition on Nutritional Value and Safety of Tomato Fruits - Dotsha Jaleel Raheem (Zanco Journal of Pure and Applied Sciences, 2024)
Fruits and vegetables are considered as health-improving contributors in the daily diet. Tomatoes are one of the most widely consumed fruits. However, the nutritional quality and safety of these fruits may not always be regulated. This research therefore worked on establishing two main aspects related to tomato consumption: the first is the relevance of visual appearance and texture to the quality and nutritional value of tomato fruits; and second to investigate the health and safety aspects of the fruits based on their elemental content. The study was conducted in Erbil - Iraq in which eight different samples were collected including local and imported fruits. The samples were investigated to determine physicochemical variables including dry matter content, total soluble solids (TSS), taste and maturity indices, total phenolic content (TPC), radical scavenging power using 2,2-diphenyl-1-picrylhydrazyl (DPPH), ascorbic acid and lycopene contents to investigate the correlation between visible physical traits and rather obscure chemical characteristics. Additionally, Inductively Coupled Plasma-Optical Emission Spectroscopy (ICP-OES) was used to analyze the elemental content and to assess the beneficial impact and/or toxic effects of these elements. The results showed significant positive correlations between taste index, lycopene content and TSS. Also, antioxidant activity was found to be more strongly influenced by ascorbic acid rather than TPC and lycopene contents. The results indicated that physical properties such as firm texture combined with deep red color and smaller fruit size are indicative of higher quality and presence of taste-enhancing and beneficial chemical components. Significant differences were found in the elemental content of the samples. Local samples were higher in essential elements. However, they also contained higher levels of cadmium (Cd) and lead (Pb). One of the imported samples contained arsenic (As). Applying the human risk assessment model (HRA), it was found that there is an appreciable carcinogenic risk from Cd in two of the local samples. Strict monitoring is therefore required to ensure that market tomatoes are safe for consumers.